Reflexões acerca da influência exercida pela (não) avaliação do PNLD sobre as atividades de leitura dos materiais didáticos de Língua Portuguesa - Alves Filho, Sebastião Carlúcio (2013)
Not very often does one hear the need to encourage reading and how this practice yields benefits to any citizen. With some frequency, also, we discuss the difficulty that students, whether from private schools or public schools, have to read written texts. Taking into account the fact that, in most cases, these students are in touch with reading almost exclusively through the learning materials they work with in the classroom, I aim, through this paper, at making an investigation on the influence exerted by the (non) evaluation of the Programa Nacional do Livro Didático (PNLD/2012) on Portuguese textbooks (LDP) distributed free to public schools and on the teaching materials used by students from private schools. That is because I believe that both the PNLD evaluation, in the case of LDP, as the lack of evaluation in the case of textbooks of private schools, influence on the content presented to students by these materials. In order to carry out this research, that it is a study case, since it takes a corpus analysis of a specific object representative of a reality, I adopt the methodological assumptions of Applied Linguistics (AL). So, categories of analysis were prepared which referentials that supported its creation are the concepts of language, reading and evaluation. In order to this, I used as theoretical framework the words of Rojo (2004, 2006 and 2009), Kleiman (1993), Silva (2009) and Solé (1998), among others who treat reading as well as Freire (1996), Luckesi (2002) and Hadji (2001) who treat the evaluation and finally Perfeito (2007), Oliveira (2008) Bakhtins (1952-53 and 1929), regarding the language. At the end of this study, it was possible to notice that the PNLD/2012 ends up not effectively exerting influence on the content presented in the Portuguese learning materials. Nor on the evaluated LDP, either, on the textbooks that do not pass by the evaluation of the Federal Government. The materials evaluated had only the minimum reading activities that include the items that propose the evaluation and are restricted to propagate a kind of teaching reading coined in the concept of language that sees it as an expression of thought, in the conception of reading that sees this practice as just a process of decoding and conception of evaluation that works as a simple way to diagnose students\' / readers difficulties.